Plant parasitic nematodes associated with pineapple cultivation (Ananas comosus) in Amazonas, Peru - Vera Obando, Nora Yessenia (2017)
The present study aimed to identify the main genera of plant parasitic nematodes associated with the pineapple crop (Ananas comosus) and their respective percentages of occurrence (frequencies) and average population densities. Soil and root samples were collected from twenty eight pineapple fields in the province of Rodríguez de Mendoza, located between 1796 and 1936 meters above sea level. Sample were processed in duplicate by the method of modified Baerman on tray, using 50 cc. of soil and 5 g of root. In soil samples, eleven genera of plant parasitic nematodes associated with pineapple crop were identified. The genus Helicotylenchus was found in all evaluated fields and presented higher population averages in soil and root samples (24.5 and 3.9 respectively). This work is the first study to identify plant parasitic nematodes in pineapple cultivation in the department of Amazonas and provides us with information that will establish future strategies for controlling these plant parasitic nematodes.